A new holistic conceptual framework for layout performance assessment. Issue 1 (21st January 2019) - Sagnak, Muhittin; Ada, Erhan; Kazancoglu, Yigit
Abstract : Purpose: Performance assessment of layouts requires a systematic approach because of its multi-objective nature. The purpose of this paper is to propose a framework to the performance assessment of layout designs. Design/methodology/approach: A layout performance assessment framework is proposed, grounded on a literature review. Then, the causal relationships and prioritization of the sub-criteria are analyzed by fuzzy Decision Making Trial and Evaluation Laboratory technique in an elevator and escalator-manufacturing firm. Findings: An integrated holistic performance assessment framework, specifically, the 7 criteria, 19 sub-criteria and 112 measures, are studied in this model which represents causal relationships and prioritization of sub-criteria. Research limitations/implications: The proposed framework can be generalized, because an integrative framework can be used in future empirical studies to analyze performance of layout design. However, the causal relationships and prioritization among sub-criteria are analyzed based on the needs and capabilities of the individual company; therefore, the results of the causal relationships are company specific. Practical implications: With this framework, the companies may assess their current layout's performance, may analyze causal relationships and prioritization of sub-criteria. Originality/value: There are very few models or frameworks regarding the performance assessment of layout designs. In this paper, a new conceptual holistic framework was proposed as three-dimensional hierarchy, which includes the main criteria, sub-criteria and the measures, respectively. Cost, flow, flexibility, surrounding environment, environment quality, time and characteristics are identified as the main criteria for the layout design performance assessment. In addition, cause-effect relationships, which will be the base for improvement of the performance, are found.